PENGARUH PENAMBAHAN PAKAN DENGAN DAPHNIA MAGNA TERHADAP TINGKAT KECERAHAN WARNA PADA PENDEDERAN IKAN KOI (CYPRINUS CARPIO VAR) DI FARM KOI KITA LOMBOK: The Effect Of Additional Feeding With Daphnia magna On The Level Of Color Brightness In Koi Fish (Cyprinus carpio var) Nursery At Our Koi Farm, Lombok - Indra Sanjaya; Aminullah Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2026)
The purpose of this study was to describe the effect of feeding with the addition of Daphnia magna on the color brightness of nursery koi (Cyprinus carpio var.) at Kita Koi Farm, Lombok. This study was a quasi-experimental study using observation, interviews, and documentation as data collection techniques. The experiment was conducted to determine the effect of feeding with the addition of Daphnia magna on the color brightness of nursery koi (Cyprinus carpio var.) at Kita Koi Farm, Lombok. The results showed that the feeding process for nursery koi was carried out in stages according to the age and digestive capacity of the fry. In the initial nursery phase, artificial feed in the form of fine flour was used as the main feed, then combined with natural Daphnia magna as a supplementary feed. Daphnia magna was fed routinely once or twice daily to increase the feeding response and activity of the fry, and to support optimal nutrient utilization. The addition of Daphnia magna as supplementary feed had a positive effect on the color brightness of the koi fry. Fry fed Daphnia magna exhibited brighter, cleaner, and more even body color compared to fry fed only artificial feed. This is thought to be related to the natural pigments (carotenoids) in Daphnia magna, which play a crucial role in the fish's color pigmentation process.